Relationship of Subjective Cognitive Impairment with Psychosocial Function and Relapse of Depressive Symptoms in Patients with Major Depressive Disorder: Analysis of Longitudinal Data from PERFORM-J - Sumiyoshi T (Dove Medical Press, 2021)
Tomiki Sumiyoshi,1 Koichiro Watanabe,2 Shinichi Noto,3 Shigeru Sakamoto,4 Yoshiya Moriguchi,5 Lene Hammer-Helmich,6 Jovelle Fernandez4 1Department of Preventive Intervention for Psychiatric Disorders, National Institute of Mental Health, National Center of Neurology and Psychiatry, Tokyo, Japan; 2Department of Neuropsychiatry, Kyorin University School of Medicine, Tokyo, Japan; 3Faculty of Rehabilitation, Niigata University of Health and Welfare, Niigata, Japan; 4Japan Medical Office, Takeda Pharmaceutical Company Limited, Tokyo, Japan; 5Medical Affairs, Lundbeck Japan KK, Tokyo, Japan; 6Medical Affairs Value Evidence, H. Lundbeck A/S, Valby, DenmarkCorrespondence: Tomiki SumiyoshiDepartment of Preventive Intervention for Psychiatric Disorders, National Institute of Mental Health, National Center of Neurology and Psychiatry, 4-1-1 Ogawahigashi, Kodaira, Tokyo, 187-8551, JapanTel +81 42 341 2711Fax +81 42 346 3569Email sumiyot@ncnp.go.jpBackground: Accumulating evidence suggests the presence of cognitive impairment in patients with major depressive disorder (MDD), which affects their psychosocial function and quality of life (QoL). PERFORM-J (Prospective Epidemiological Research on Functioning Outcomes Related to MDD in Japan) is an observational, multicenter study to assess longitudinal changes in depressive symptoms, psychomotor speed, subjective cognitive function, and psychosocial function.Methods: Five hundred and eighteen Japanese outpatients with MDD initiating new antidepressant monotherapy (first-line or switch from previous drug) as part of their routine medical care participated in this study. Assessments at baseline and over the 6-month observation period included physician-rated depression severity (Montgomery–Åsberg Depression Rating Scale), psychomotor speed (Digit Symbol Substitution Test; DSST), subjective cognition (Perceived Deficits Questionnaire–Depression), psychosocial function (Sheehan Disability Scale), and QoL (EuroQol-5 Dimension-5 Level).Results: Antidepressant treatment for 6 months improved depressive symptoms and subjective cognitive impairment (cognitive complaints), whereas psychomotor speed remained impaired (ie, DSST total score was > 1 standard deviation below the norm) in 35.6% of patients at 6 months. Impairment of subjective cognition, but not psychomotor speed at month 2 was associated with poor psychosocial function and QoL at 6 months. There was a trend for higher relapse rates at 6 months in patients with greater subjective cognitive impairment at 2 months.Conclusion: These findings highlight the importance of evaluating cognitive difficulties to predict long-term outcomes in patients with MDD. Early intervention for cognitive complaints may decrease the relapse rate, which warrants further study.Keywords: cognition, depression, functional outcome, quality of life, Japan